Simultaneous development of Guillain–Barre syndrome and bacterial meningitis as complications of pneumonia caused by Staphylococcus aureus: a case report - Yuliia Solodovnikova; Anastasiia Revurko; Svitlana Oliinyk; Anatoliy Son (Journal of Medical Case Reports)
Abstract Background Guillain–Barre syndrome is an acquired inflammatory polyradiculoneuropathy that often follows gastrointestinal infection. A review of available literature revealed only few cases where Guillain–Barre syndrome developed after different types of meningitis. Furthermore, there are isolated cases of Guillain–Barre syndrome combined with meningeal irritation. This is the first reported case of Guillain–Barre syndrome and bacterial meningitis occurring simultaneously as complications of community-acquired pneumonia. Case presentation We report the case of a 77-year-old Ukrainian male patient who presented to the hospital with clinical symptoms of pneumonia. Over the next day, he developed clinical symptoms of acute symmetric ascending flaccid tetraparesis. A few days later, synkinesis-like movements appeared in the paralyzed lower limbs. Microbiological studies of the cerebrospinal fluid identified antibiotic-sensitive Staphylococcus aureus. The patient received treatment with intravenous immunoglobulin and combination antibacterial therapy. The patient was discharged with improvement. Conclusion In this case, a potentially life-threatening condition, such as bacterial meningitis, was asymptomatic and clinically unrecognized. It is important to recognize atypical cases of Guillain–Barre syndrome to achieve early diagnosis and treatment.